Decision table languages and systems - Metzner, John R.; Barnes Bruch H. (Academic Press, 1977)
ACM Monograph Series: Decision Table Languages and Systems focuses on linguistic examination of decision tables and survey of the features of existing decision table languages and systems.The book first offers information on semiotics, programming language features, and generalization.